Career Anchor In The Concept Of Self-Employment Catholic High School Teacher - Meiliani Meiliani; Yulius Paskalis Harmoko; Oktarina Christianti (UNIB Press, 2023)
Career anchors is strongly important to guide one’s internal career orientation that employ their talents/competent, motives/needs, and values in the various types of jobs, including teachers. The study aimed to describe the career anchors chosen by Catholic high schools’ teachers employed by Tarakanita fondation. Data were gathered from 302 teachers from 10 high schools and 2 colleges by distributing online survey questionnaires. A set of questionnaires was sent via emails directly to each teacher. Discriptive statistics of mean and percentage were applied to analisy the data gathered. The results showed that the highest rank of dominant career anchor was the economic security anchor, in contrary to it was supposed to be, that was the service anchor. None had multiple career anchors. It means that each teacher still focused on their basic needs in pursing her/his careers. This implies that either private or government individuals have the same career orientation in contrast to the original concept developed by Schein.